Socio-economic dynamics and innovative technologies affecting health-related lipid content in diets: Implications on global food and nutrition security - Nantapo, Carlos W.T.; Muchenje, Voster; Nkukwana, Thobela T.; Hugo, Arnold; Descalzo, Adriana Maria; Grigioni, Gabriela Maria; Hoffman, Louwrens C. (2018)
The recent increase in human population coupled with rural-to-urban migration has led to challenges in managing a balanced diet in both food ‘secure’ and food ‘insecure’ regions. As a result of this geographic phenomenon, the human population continues to suffer from caloric-related conditions and diseases, including obesity and coronary heart diseases. In addition, fat and fatty acid composition of the diet has come under severe attack from the media and different human nutrition corridors in the past as they have been implicated in aiding the increase in cases of coronary heart diseases despite their important roles in cellular functions. In this view, fat and fatty acids is of great significance to the modern society, which aims at balancing their dietary proportions for efficient functionality of the human body systems. To improve food and nutrition, understanding the physiological function of the body and biochemical function of the fatty acids and polar lipids and getting a clearer view of the socio-economic aspects surrounding food consumption is also important. However, to further enhance the utilisation of fats accessed from diets, it is important to highlight significant current innovative technologies used to improve food fatty acid profiles and the influence of media on dietary and food consumption patterns. This review discusses the significance of health-related fatty acids, socio-economic aspects governing their presence in food and consumption, and how all these factors have a bearing on achieving the goal of human health, well-being and food and nutrition security.